2003
DOI: 10.1039/b306037n
|View full text |Cite
|
Sign up to set email alerts
|

Branched methacrylate copolymers from multifunctional comonomers: the effect of multifunctional monomer functionality on polymer architecture and properties

Abstract: Soluble. branched (meth)acrylic copolymers have been synthesised via facile, one-step, batch solution polymerisations taken to high conversion. Methyl methacrylate has been copolymerised with a number of multifunctional comonomers using a chain transfer agent to prevent gelation. A variety of soluble, branched copolymer architectures have been synthesised using multifunctional monomers containing between two and six acrylate functional groups. Independent of polymer composition, all copolymers were proven to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 28 publications
1
114
0
Order By: Relevance
“…In the latter case, as expected, all reactions showed evidence of early crosslinking, leading to insoluble material. This provides supplementary experimental evidence that the synthesis of soluble branched polymers by free-radical copolymerisation seems impossible when the reaction is taken to high conversion [1]. Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In the latter case, as expected, all reactions showed evidence of early crosslinking, leading to insoluble material. This provides supplementary experimental evidence that the synthesis of soluble branched polymers by free-radical copolymerisation seems impossible when the reaction is taken to high conversion [1]. Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Their strategy involves the conventional free radical polymerization of a vinyl monomer, in the presence of a multifunctional vinyl comonomer and a chain transfer agent to prevent crosslinking [1][2][3][4][5][6]. Besides using conventional chain transfer agents in the synthesis of branched polymers, Sherrington's group, in collaboration with Armes' group, also applied copper mediated living radical polymerization (LRP) and group transfer polymerization (GTP) to the synthesis of soluble branched polymers in facile one-pot reactions, and obtained well-controlled hyperbranched architectures [4].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] A trend of decreased values of a with increased branching is seen when comparing the linear polymers to the branched four-arm stars and hyperstars (Table 1). This effect is the result of the polymers becoming denser when the branching increases.…”
Section: Secmentioning
confidence: 99%
“…Since then we and our industrial collaborators [6][7][8] have developed the methodology extensively in the case of branched poly(methyl methacrylate)s and have established some key principles in formulating polymerisations to optimise branching versus cross-linking [9]. Perhaps most importantly we have demonstrated that the number of primary linear polymer chains is essentially controlled by the number of moles of transfer agent used in excess relative to the initiator, and that providing the mole ratio of branching difunctional comonomer/transfer agent is kept 61 cross-linking can be avoided.…”
Section: Introductionmentioning
confidence: 99%